Platybracon Yang et al. (2008) (Hymenoptera: Braconidae), junior homonymy and subjective synonymy—a systematic and nomenclatural note - Kittel, Rebecca N.; Quicke, Donald L. J. (Zootaxa, 2015)
Yang et al. (2008) described a distinctive, small braconine wasp, Platybracon sinicus, from China as a new genus and new species. They discussed similarities with other braconine genera and to which genus it would belong to when using the only available key to the Braconinae (Quicke, 1987). However, they failed to notice that their genus name Platybracon would be a junior homonym of Platybracon Szépligeti, 1900. Additionally, Platybracon is itself a junior subjective synonym of Chaoilta Cameron 1899, also a member of the Braconinae, synonymised by Baltazar, 1966 and upheld by Quicke (1987). Platybracon sinicus described by Yang et al. does not belong to the genus Chaoilta, which belongs to the Aphrastobraconini (sensu van Achterberg 1989) but instead is a member of the Plesiobracon genus group of the Braconini.